Direct ozone production rate measurements and their use in assessing ozone source and receptor regions for Houston in 2013. (August 2015) - Baier, Bianca C.; Brune, William H.; Lefer, Barry L.; Miller, David O.; Martins, Douglas K.
Abstract: Mitigating ozone pollution involves reducing ozone production and relies on complex air-quality models to design reduction strategies and determine their effectiveness. However, modeled ozone does not always agree with observations. A complementary approach is to measure the ozone production rate directly, leading to the development of the Measurement of Ozone Production Sensor (MOPS). Two improved second-generation MOPSv2s were deployed for NASA's DISCOVER-AQ field campaign in September 2013 at the University of Houston, 5 km south of downtown, and Smith Point, at the mouth of the Houston Ship Channel. Median September P(O3 ) was low, consistent with the observed ambient ozone. The MOPSv2s provided statistically similar results when they were compared for 8 day sat the University of Houston. October measurements yielded a median ozone production rate of 27 ± 11 ppbv hr −1, falling within the range of calculated P(O3 ) from prior Houston field campaigns in 2006 and 2009. Additionally, diurnal patterns are similar to model-derived ozone production from these previous campaigns. An advection analysis for a high ozone event on 25 September 2013 indicates that the Houston site was in a local ozone source region, while Smith Point ozone was likely enhanced by transport from other areas. Highlights: We directly measure ozone production rates at two areas in the Houston region. September production rates are low, consistent with ambient ozone levels. An advection analysis indicates ozone source and receptor regions.